Campo e cidade, caminhos entrecruzados: uma leitura de crônicas de Rachel de Queiroz - Santana, Patricia Costa de (2016)
This dissertation is a study of the relationship between country and city in Rachel de Queiroz chronics (1910-2003) in order to understand the similarities between the place, the landscape and the manifestation of the man who seeks to affirm their cultural identity. Chronic relies on everyday events, allowing to know the context of a particular time and for this reason the choice of this kind as the object of this research. This work shows that the social and economic context of the twentieth century is present in chronic composition of Rachel de Queiroz, as a relevant contribution to Brazilian literature. This theme is related to the importance of intrinsic images to the field / city in chronic, the way of the dialogue, fit and at the same time, differ. Finally, this study is an attempt to expand the critical analysis of the writer, as many jobs are directed to gender studies in its romances, confirming its importance in the Brazilian scene of the twentieth century.